(3OjhGf RgjQ Hf CHj Sdeis - (3RgjQ Hf CHj oSrdnej QHjYI Hf QjGM GdeRfj GdeVQjs
(3ChdgG (B:s
(3bGd RgjQ Hf CHj Sdei jeOM GdMGQK Hf Yha hgQe Hf GdMGQK Hf SfGf GdeQi(B: (3Cef Ce Chai OefI de Jcde HMheGfI GdOQGL aGdeJKde s
(3BNQgG (B:s
(3CjSGQ UOb eG YdeJge YOO GdTJGA hbdI GdCfhGA s
(3hQO CjVkG JMJ Qbe (B502(3, (B503(3, (B551(3, (B1302(3, (B1303(3, (B1304(3, (B1866(3, (B1867(3, (B2087(3, (B2088s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B52 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B186s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B112 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B791s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1/406) s
Keywords: (3GdCOHs